Fostering consumer engagement with marketer-generated content: the role of content-generating devices and content features. Issue 7 (25th March 2022) - Yang, Qiang; Li, Hongxiu; Lin, Yanqing; Jiang, Yushi; Huo, Jiale
Abstract : Purpose: This research explores the impacts of content-generating devices (mobile phones versus personal computers) and content features (social content and achievement content) on consumer engagement with marketer-generated content (MGC) on social media. It also examines these factors' interaction effects on consumer engagement. Design/methodology/approach: The study analyzed MGC that 210 companies had posted to Sina Weibo over three years, testing the study's proposed model with negative binomial regression analysis. Findings: The study's results show that MGC generated via mobile phones attracts more consumer engagement than MGC generated via personal computers. MGC with more social features attracts more consumer engagement, whereas MGC with more achievement features reduces consumer engagement. The authors also found that MGC with more social features generated via mobile phones and MGC with more achievement features generated via personal computers lead to more consumer engagement due to the congruency of the construal level of psychological distance. Originality/value: This research enriches the literature by exploring the effects of content-generating devices and content features on consumer engagement in the MGC context, which extends the research on consumer engagement with social media from the context of user-generated content to the MGC.